Reflections on Phelan’s Neoliberalism, Media, and the Political - Thomas Klikauer (tripleC: Communication, Capitalism & Critique)
Seeking to overcome the “Blindspot of Western Marxism”, Phelan’s insightful book discusses neo-liberalism, the media, and the political by defacing neo-liberalism, analysing journalism using neo-liberal media control of New Zealand and Ireland (the so-called Celtic Tiger) as well as the case of “Climategate” as prime examples. The core argument of the book is to relate neo-liberalism to media and the way it colonises the public, which Phelan calls “the political”. On the example of human freedom, Phelan shows for example, how neo-liberalism has defaced freedom by focusing on the negative—as the absence of state interference. Phelan also shows how freedom became a one-dimensionality being associated with market freedom. With a most illuminating chapter on journalism under neo-liberalism, Phelan concludes that it is not moralising that challenges neo-liberalism but instead what is demanded is using people’s experience of everyday neo-liberalism leading to a disidentification with neo-liberalism’s one-dimensional and oppressive ideology.